Clinical evaluation of implant osseointegration with platelet rich plasma and lyophilizated bone in patients with dento alveolar loss due to trauma in the anterior area: first phase - Naranjo-R., Rodrigo Felipe; Duque-S., Francisco Levi; Correa-T., Diana Marcela; Sanín-G., Luisa Fernanda (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Introduction: the aim of the present study was to evaluate clinically and radiographically the osseointegration of implants with bone regeneration by platelet rich plasma (PRP) and freeze-dried bone, placed in patients with dentoalveolar loss by trauma in the anterior region, during the firsts stages of soft tissue healing, treated at the Hospital Universitario San Vicente de Paúl (Medellín-Colombia) Methods: 15 implants were placed in six patients who suffered tooth loss due to trauma in the anterior maxillary and mandible area. The placement of the implants was performed between eight to twenty days after trauma, and they were submerged four months in the mandible and six months in the maxilla. A clinical and radiographic evaluation was done at the second-stage surgery to determine osseointegration. Results: osseointegration percentage was 93.3% (14 implants). An implant failed (6.7%) and showed mobility without any infection signs or radiolucency, which suggests that failure, could be the result of surgical trauma. Conclusion: the present study showed that osseointegration percentage in patients with dentoalveolar trauma was good with the utilization of PRP according to the present protocol.